Artificial intelligence : a modern approach - Russell, Stuart J. (Stuart Jonathan); Norvig, Peter (Harlow : Pearson, 2022)
"Updated edition of popular textbook on Artificial Intelligence. This edition specific looks at ways of keeping artificial intelligence under control"--
Includes bibliographical references and index.
CSE
Keywords: Artificial intelligence; Computer science